Comparative study of the antioxidant properties of organic and inorganic melissa - Tkachenko, Alina (Technology audit and production reserves, 2023)
The object of research is organic and inorganic lemon balm. The subject of research is the antioxidant properties of these plants. One of the most problematic areas is that organic products have a slightly different chemical composition, which is due to the lack of fertilizers during their cultivation. The research hypothesis is that organic plants naturally release more phenols and polyphenols, which are needed to fight pests. At the same time, polyphenol compounds have antioxidant properties. The work investigated the total content of polyphenols in organic and inorganic lemon balm. The content of polyphenols in terms of gallic acid was determined by the spectrophotometric method by reaction with the Folin-Chocalteu reagent. In order to determine the antioxidant properties, the content of the peroxide number and the acid number of the fatty base during storage were determined. As a fat base, a mixture of organic butter and organic rye oil was chosen in a ratio of 75:25. Dried lemon balm was added in the amount of 4 % to the mass of fat. Changes in the fat base were determined in three samples: without the addition of lemon balm, with the addition of dried inorganic and organic lemon balm. The samples were stored in a thermostat at a temperature of 50 °C for 10 days. Studies were conducted every 2 days. The amount of peroxides was determined by the iodometric method. The acid number content was determined every 5 days by the titration method. It has been established that organic lemon balm has better antioxidant properties. This is due to the content of polyphenolic substances. So, the content of polyphenols in ordinary lemon balm is 14.1 mg/g, and in organic – 26.5 mg/g. Research has established that the value of the peroxide number after 10 days of storage was 17 ½O for the sample with the addition of organic lemon balm and 22 ½O for the sample with the addition of ordinary lemon balm. The sample without the addition of lemon balm had a value of 25 ½O. The value of acid number of fat on the tenth day of storage was 1.4 for the sample with the addition of inorganic lemon balm and 1.1 for the sample with the addition of organic lemon balm. Further research is planned to be devoted to the effect of plant organic antioxidants on the lipid fraction of food products.